Bimbingan Konseling Bagi Siswa Cerdas dan Berbakat - Wicaksono, Luhur (Jurnal Pembelajaran Prospektif, 2016)
Intelligent and talented students are individuals (learners) clasified as the upper classification having above average intelligence level. Their above average abilities make them have special needs and characteristics. It is necessary to handle counseling to provide solutions of avoiding obstacles on the students themselves or against their friends. With the help of counseling the students are given assistance through the program and suitable techniques in order to develop optimally in accordance with their potentials.